Comprehensive Review of Phytochemical Constituents, Pharmacological Properties, and Clinical Applications of Prunus mume - Gong, Xue-Peng; Tang, Ying; Song, Yuan-Yuan; Du, Guang; Li, Juan (Frontiers in Pharmacology, 2021)
Prunus mume is one of the most ancient medicinal herbs and health foods commonly used in Asian countries. It is widely used as a constituent of many medicinal preparations and as a food ingredient for its beneficial health effects. In this review, we retrieved reports from PubMed, Embase, Scopus, and SciFinder databases, to collect extensive scientific evidence on the phytochemical constituents, pharmacological properties, and clinical applications of Prunus mume. The literature review shows approximately 192 compounds have been isolated from different parts of the plant, and their molecular structures have been identified. The pharmacological properties of the plant, including anti-diabetic, liver-protective, antitumor, antimicrobial, antioxidant, and anti-inflammatory activities, as well as their underlying mechanisms, have been clarified by in vitro and in vivo studies. Clinical studies, although very limited, have been highlighted to provide a reference for further exploration on therapeutic applications of the plant.